2018
DOI: 10.3390/en11071644
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Imports and Exports on the Evolution of Greenhouse Gas Emissions: The Case for the European Union

Abstract: Part of a country's emissions are caused by producing goods for export to other countries, while a country's own needs also generate emissions in other parts of the world that are associated with the products they import. Our interest was to evaluate the influence of imports and exports of goods and services on greenhouse gas (GHG) emissions in a data panel composed of 30 countries over 21 years. We included as control variables the gross domestic product per capita, employment, an indicator of the economic cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…This shows that the existing growth process is not efficient and environmentally friendly due to high pollutants produced in the development process for economic growth. High CO 2 emissions occur because activities, such as investment, can move economic growth and it will require large energy consumption (Shahbaz et al (2019); Nasir et al (2019)), as well as, production and consumption which represented by the export and import of the country (Hossain (2011);Hossain (2012); Pié et al (2018); Dong et al (2019)). The findings shows that Malaysia, Indonesia, Iran, Saudi Arabia, Thailand, and India have large intercept values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that the existing growth process is not efficient and environmentally friendly due to high pollutants produced in the development process for economic growth. High CO 2 emissions occur because activities, such as investment, can move economic growth and it will require large energy consumption (Shahbaz et al (2019); Nasir et al (2019)), as well as, production and consumption which represented by the export and import of the country (Hossain (2011);Hossain (2012); Pié et al (2018); Dong et al (2019)). The findings shows that Malaysia, Indonesia, Iran, Saudi Arabia, Thailand, and India have large intercept values.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in the European Union show that CO 2 emissions will be rise if country do more imports. Otherwise, carbon emission will be pull down with higher exports (Pié et al, 2018). Especially with the existence of trade integration (Ahmed et al, 2017).…”
Section: Studies With Co 2 Emission and International Tradementioning
confidence: 99%
“…Similar to the processing link, an impact on GHG emission was also identified due to the import of legumes. Higher imports result in higher GHG emissions [72], which have an impact on two levels: firstly, the carbon costs of land use change for legume grain production (e.g., in deforested rainforest areas) is offshored; secondly, less domestically grown legumes are cultivated. Such a displacement is favourable for non-leguminous, N-fertilizer-demanding crops.…”
Section: Focus Area: Pressures On the Environment (Environmental Pillar)mentioning
confidence: 99%
“…Exports and imports enhance economic growth, and economic growth leads to energy demand and an increase in CO 2 emissions (Sánchez-Chóliz and Duarte 2004). After an investigation of 30 countries in the European Union between 1991 and 2012, Pie et al (2018) found that the more a country imports, the higher the country's CO 2 emissions will be.…”
Section: Tertiary Sector and Co 2 Emissionsmentioning
confidence: 99%